2021
DOI: 10.1002/pbc.28913
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive functioning and academic achievement in survivors of childhood acute lymphoblastic leukemia: A report from the Children's Oncology Group

Abstract: Purpose To characterize academic and adaptive skill outcomes in survivors of high‐risk B‐lineage acute lymphoblastic leukemia (HR B‐ALL). Methods Participants were 178 patients enrolled on a nontherapeutic clinical trial that aimed to characterize neurocognitive and functional outcomes (ie, academic achievement and adaptive skills) following treatment for childhood HR B‐ALL. Eligible patients were treated on Children's Oncology Group AALL0232 clinical trial that included two treatment randomizations: methotrex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 25 publications
2
30
0
Order By: Relevance
“… 9 , 15 For example, Jacola and colleagues reported that survivors diagnosed prior to age 10 had lower math scores than survivors who were diagnosed at an older age. 10 Likewise, Harshman and colleagues showed that survivors diagnosed prior to the age of 5 years old had reduced academic achievement relative to those diagnosed after the age of 5. 14 By contrast, we observed no significant association between academic outcomes and age at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 9 , 15 For example, Jacola and colleagues reported that survivors diagnosed prior to age 10 had lower math scores than survivors who were diagnosed at an older age. 10 Likewise, Harshman and colleagues showed that survivors diagnosed prior to the age of 5 years old had reduced academic achievement relative to those diagnosed after the age of 5. 14 By contrast, we observed no significant association between academic outcomes and age at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with previous literature showing that ALL survivors who were covered through public insurance were at higher risk of exhibiting neurocognitive difficulties. 10 , 16 Comparable metrics are applied to determine eligibility for US public health insurance coverage. We opted to use free/reduced lunch because it was collected at the same time as our outcome measures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations